2008
DOI: 10.1177/0003319708321479
|View full text |Cite
|
Sign up to set email alerts
|

Alternate Site Pacing in Patients at Risk for Heart Failure

Abstract: Cardiac pacing from the right ventricular apex is the most common site of cardiac pacing. During the last decade, several studies demonstrated the harmful effects of the iatrogenic left bundle branch block, which is observed in cardiac pacing from the right ven- tricular apex. These observations led to an interest in alternative right ventricular pacing sites aiming to achieve a more “physiological” pattern of ventricular activation. Alternate site pacing may involve His bun- dle, other right ventricular sites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Furthermore, clinical trials have shown that RVA pacing can cause electro-mechanical contraction of the left and right ventricles to be asynchronous. Long-term RVA pacing can cause cardiac histologic and electrical remodeling, abnormal myocardial contractile pattern, hemodynamic disorder, and ultimately cardiac insufficiency, there is also the risk of atrial fibrillation (AF) and heart failure (HF), which increases the rate of hospitalization and mortality ( Manolis et al, 2008 ; Miranda et al, 2012 ; Alhous et al, 2015 ). So optimization of right ventricular pacing site becomes an important object of pacing electrophysiology.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, clinical trials have shown that RVA pacing can cause electro-mechanical contraction of the left and right ventricles to be asynchronous. Long-term RVA pacing can cause cardiac histologic and electrical remodeling, abnormal myocardial contractile pattern, hemodynamic disorder, and ultimately cardiac insufficiency, there is also the risk of atrial fibrillation (AF) and heart failure (HF), which increases the rate of hospitalization and mortality ( Manolis et al, 2008 ; Miranda et al, 2012 ; Alhous et al, 2015 ). So optimization of right ventricular pacing site becomes an important object of pacing electrophysiology.…”
Section: Introductionmentioning
confidence: 99%